Inhibitory effects of eucalyptol and limonene on the photosynthetic abilities in Chlorella vulgaris (Chlorophyceae). Issue 6 (1st November 2016) - Zhao, Jingxian; Yang, Lin; Zhou, Lv; Bai, Yan; Wang, Bin; Hou, Ping; Xu, Qinghuan; Yang, Wangting; Zuo, Zhaojiang
Abstract: In aquatic ecosystems, volatile organic compounds (VOCs) from cyanobacteria have allelopathic effects on other algae. Terpenoids are among the key VOCs released from cyanobacteria and are thought to act as the allelopathic agents. However, there is limited information about the specific terpenoid that can act as allelopathic agent. To reveal the allelopathic effects of eucalyptol and limonene, two of the main terpenoids in cyanobacteria VOCs and the impacts of the two compounds on Chlorella vulgaris cell growth, photosynthetic pigment absorption spectra and photosynthetic abilities were investigated. In the treatment with the two compounds, the inhibition on the cell growth was enhanced with increasing the compound concentration, and the whole cells were even killed by 4 mM limonene. Meanwhile, a reduction was found in photosynthetic pigment absorption peaks at 413, 433, 457 and 663 nm. The components of photosynthetic pigments were degraded, and the disappearance of xanthophyll was observed in 1.6 mM limonene treatment. When C. vulgaris was treated with eucalyptol and limonene, the fluorescence intensity from O to P was lower than that in the control, suggesting that the two compounds had inhibitory effects on the donor and acceptor side of photosystem II (PSII). The analysis of chlorophyll fluorescence transient parameters indicated that eucalyptol and limonene can reduce the concentration of PSII reaction centers, inhibit the quantum production and electron transport in PSII, and promote the absorbed light energy to dissipate as heat. Therefore, eucalyptol and limonene might play allelopathic roles in cyanobacterial VOCs by inducing degradation of photosynthetic pigments and reducing photosynthetic abilities in other algae.